Circular polarized active microstrip antenna for commercial GPS application - Thiagarajah, Sharlene; Mohd. Ali, Borhanuddin; Habaebi, Mohamed Hadi (2000)
A circularly polarized microstrip antenna was investigated for a commercial land-based GPS application mainly due to its polarization potential and attractive physical properties. Both a circular and square patch design were fabricated and analyzed to investigate design and fabrication sensitivity to geometry. The effect of smaller patch size on performance was also investigated. The inherently low gain characteristic of the patch antenna was improved by integrating an active circuit with the patch. At 1575.42 MHz, gain of 16dB and input return loss, Sll > -30 dB was obtained with the active patch. Measured performance of several patch designs and GPS satellite acquisition data are presented.